Food intake in fish (Blackwell Science, 2001)
This important book, which has arisen out of a European Union COST programme, illustrates how insights into the biological and environmental factors that underlie the feeding responses of fish. Food Intake in Fish contains carefully edited contributions from internationally recognised scientists, providing a book that is an invaluable tool and reference to all those involved in aquaculture